1997
DOI: 10.1083/jcb.139.4.875
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of NSF ATPase Activity by α-SNAP Is Required for SNARE Complex Disassembly and Exocytosis

Abstract: N-ethylmaleimide–sensitive fusion protein (NSF) and α-SNAP play key roles in vesicular traffic through the secretory pathway. In this study, NH2- and COOH-terminal truncation mutants of α-SNAP were assayed for ability to bind NSF and stimulate its ATPase activity. Deletion of up to 160 NH2-terminal amino acids had little effect on the ability of α-SNAP to stimulate the ATPase activity of NSF. However, deletion of as few as 10 COOH-terminal amino acids resulted in a marked decrease. Both NH2-terminal (1–160) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
179
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(193 citation statements)
references
References 40 publications
13
179
0
1
Order By: Relevance
“…Antibodies against Sec18p and removal of ATP prevent vacuole docking; both of these treatments inhibit cis-SNARE complex disassembly (5, 50) and would be expected to block formation of 3Q cis-SNARE or 3Q:1R transSNARE complexes. In an in vitro assay for formation of the vesicular tubular cluster, an intermediate in transport from the endoplasmic reticulum (ER) to the Golgi apparatus, antibodies against Syntaxin 5, a homolog of Vam3p, inhibit vesicle ''coisolation,'' as does addition of a dominant negative mutant of ␣-SNAP that blocks NSF SNARE complex disassembly activity (58,59). Docking of synaptic vesicles to the plasma membrane in Caenorhabditis elegans neuromuscular junctions also requires syntaxin (60).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against Sec18p and removal of ATP prevent vacuole docking; both of these treatments inhibit cis-SNARE complex disassembly (5, 50) and would be expected to block formation of 3Q cis-SNARE or 3Q:1R transSNARE complexes. In an in vitro assay for formation of the vesicular tubular cluster, an intermediate in transport from the endoplasmic reticulum (ER) to the Golgi apparatus, antibodies against Syntaxin 5, a homolog of Vam3p, inhibit vesicle ''coisolation,'' as does addition of a dominant negative mutant of ␣-SNAP that blocks NSF SNARE complex disassembly activity (58,59). Docking of synaptic vesicles to the plasma membrane in Caenorhabditis elegans neuromuscular junctions also requires syntaxin (60).…”
Section: Discussionmentioning
confidence: 99%
“…All these recombinant proteins were originally in pQE9 vectors. In addition, we used the single point mutation Leu-294 of ␣-SNAP, ␣-SNAP L294A (35), which was generated earlier (34). The following constructs were newly generated for this study: a deletion variant of ␣-SNAP in which the first 32 residues were removed (␣-SNAP del (aa 33-295)) and an ␣-SNAP mutant in which the two phenylalanines in positions 27 and 28 were mutated to serines (␣-SNAP F27S,F28S ).…”
Section: Methodsmentioning
confidence: 99%
“…The finding that the SNARE complex/SNARE monomer ratio of SNAP P2 heterozygotes exceeds that of SNAP deficiency heterozygotes suggests that the SNAP P2 mutation represents a dominant negative allele. Previous analysis has shown that a mutationally altered version of mammalian SNAP that bears an amino acid substitution at the site immediately adjacent to the codon affected by the SNAP P2 mutation dominantly inhibits exocytosis in adrenal chromaffin cells (Barnard et al, 1997;Graham and Burgoyne, 2000). This derivative is thought to act by inhibiting the activation of NSF, and the dominant negative behavior of the SNAP P2 allele may result from a similar inhibitory effect on NSF.…”
Section: Altered Snap Dosage Affects Snare Complex Metabolism and Synmentioning
confidence: 99%